2019
DOI: 10.3390/md17080473
|View full text |Cite
|
Sign up to set email alerts
|

Padina pavonica Extract Promotes In Vitro Differentiation and Functionality of Human Primary Osteoblasts

Abstract: Marine algae have gained much importance in the development of nutraceutical products due to their high content of bioactive compounds. In this work, we investigated the activity of Padina pavonica with the aim to demonstrate the pro-osteogenic ability of its extract on human primary osteoblast (HOb). Our data indicated that the acetonic extract of P. pavonica (EPP) is a safe product as it did not show any effect on osteoblast viability. At the same time, EPP showed to possess a beneficial effect on HOb functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Previously, we had demonstrated that extract of Padina pavonica [ 27 , 28 ] alleviated neurodegenerative phenotypes in fruit fly models of AD and PD when added as a food supplement [ 32 ]. In separate studies, we had also shown that pathogenic aggregates of three amyloid-forming proteins involved in the major brain neurodegenerative diseases—Aβ42, α-syn and tau—were highly damaging to mitochondria and the mitochondrial double-membrane.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we had demonstrated that extract of Padina pavonica [ 27 , 28 ] alleviated neurodegenerative phenotypes in fruit fly models of AD and PD when added as a food supplement [ 32 ]. In separate studies, we had also shown that pathogenic aggregates of three amyloid-forming proteins involved in the major brain neurodegenerative diseases—Aβ42, α-syn and tau—were highly damaging to mitochondria and the mitochondrial double-membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Extract derived from the alga Padina pavonica (PPE) was supplied by the Institute of Cellular Pharmacology (ICP Concepts Ltd., Mosta Technopark, Malta). PPE was produced and chemically characterized as described previously [ 27 , 28 , 65 ]. Briefly, the seaweed was dried and milled before solid-liquid extraction was carried out by the Soxhlet extraction method using acetone as solvent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidant fucoidans from Dictyota mertensii protect pro-osteoblastic cells under oxidative stress by deregulating osteoblast activity [217]. Furthermore, Padina pavonica promotes pro-osteogenic effects by enhancing osteoblast differentiation and subsequent mineralization, as well as by regulating the expression of earlier osteoblast-specific markers [218]. In contrast, fucoxanthin from Laminaria digitata and Ascophyllum nodosum extract showed low pro-osteogenic activity in the two cell types tested [11].…”
Section: Phenolic Extract In Vitro and In Vivomentioning
confidence: 99%
“…Promoted osteoblast-like cell mineralization Increased opercular bone area [222] Some marine algae have been investigated for their beneficial effects as osteogenic agents because of their important minerals, such as manganese, zinc, calcium, and amino acids, which can promote bone metabolism [223]. Bone-forming cells include osteoblasts, osteocytes, and bone-lining cells, whereas osteoclasts participate in bone resorption [218]. Red seaweeds have been reported to have osteoprotective effects on osteogenic differentiation.…”
Section: Phenolic Extract In Vitro and In Vivomentioning
confidence: 99%